LOVE SCAMS ISSUES IN MALAYSIA: HOW TO OVERCOME IT FROM AN ISLAMIC PERSPECTIVE - Ameera Ismail; Hanin Hazwani Suhardi; Balqis Mohd Ramli; Fatin Nabilah Mohd Yunus; Wan Noor Hazlina Wan Jusoh (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Love scams are nothing new, as this case has been ongoing since 2008 to the present day. Malaysia is one of the countries that has been identified as a destination or base for this cybercrime syndicate. In Malaysia, 1,535 love scams were reported in 2019, with a total loss of RM79.11 million, while 1582 cases were reported in 2020, with a total loss of RM58.33 million. The common target of a scammer who is easily duped consists of highly educated, still-single professional women with a high income. This increasing number of cases demonstrates that the community must remain vigilant and pay close attention to these cases. Therefore, this paper aimed at finding the factors, impacts and solutions for this issue from an Islamic perspective. Library research is used to discuss the issue from the three dimensions. It is found that the increasing use of social media is one of the main contributing factors to the existence of love scams. The victims of the love scam will thereafter suffer a significant financial loss. The main solution to this problem is to get closer to Allah SWT and family members, as this can help Muslims avoid becoming victims of love scams.